A Construction of Outcome-Based Education Model for Basketball Skills Course in Junior High School at Thawi Watthana District - Supsutthiphon, Chuchat; Siriphan, Chanchai (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: Outcome-based education is an educational concept that emphasizes goals or outcomes at the end of a period of instruction. Every student must put the knowledge into practice correctly and appropriately. The objectives of this study aimed to develop and construct a teaching model for outcome-based education in the course basketball skills of junior high school students in the Thawi Watthana district. Methods: Methodology: The research work is divided into four phases. Phase 1: study basic information problems in organizing teaching and learning construction teaching model outcome-based education in the course basketball skills of junior high school students in Thawi Watthana district from 309 students and 30 teachers in the physical education category Phase 2: Interviewing seven experts to develop a draft model Phase 3: Create a teaching model using the Delphi method from a total of 19 experts, divided into 2 rounds. Phase 4: Image evaluation from 7 experts for construction teaching model outcome-based education in the course basketball skills of junior high school students in Thawi Watthana district. Results: Analysis revealed the need for a comprehensive basketball teaching model with four primary elements (basketball theory, basketball skills, physical adaptability, and social adaptability), further divided into 12 secondary and 34 tertiary elements. Each segment is tailored to specific outcome objectives, emphasizing cognitive understanding, skill mastery, physical fitness, and social adaptation. Discussion: Construction teaching model outcome-based education in the course basketball skills of junior high school students in Thawi Watthana district. The curriculum fosters not only the enhancement of basketball-specific knowledge and skills but also promotes overall student development, accentuating theoretical comprehension, practical application, physical well-being, and social adaptability. Conclusion: The outcome-oriented teaching approach in the junior high school basketball skills course in the Thawi Watthana district emphasizes a two-tier model, focusing on basketball theory and skills. The model aims to cultivate expertise that can be applied in team play, enhancing physical fitness and social adaptability.